Mannose-binding lectin (MBL) as prognostic factor in paediatric oncology patients - Frakking, F N J (Blackwell Science Inc, 2011)
Deficiency of mannose-binding lectin (MBL) has been suggested to influence duration of febrile neutropenia and prognosis in paediatric oncology patients. However, there is no consensus on the definition of MBL deficiency. In a cohort of children with cancer, we investigated (i) how to determine MBL deficiency and (ii) whether MBL is a prognostic factor for disease severity. In 222 paediatric oncology patients, 92 healthy children and 194 healthy adults, MBL plasma levels and MBL2 genotype (wild-type: A, variant: O) were determined. Event-free survival (EFS), overall survival (OS) and paediatric intensive care unit (PICU) admissions were recorded prospectively. In febrile neutropenic patients admitted to the PICU, disease severity was assessed by clinical, microbiological and laboratory parameters. An optimal cut-off value for MBL deficiency was determined to be < 0·20 µg/ml. Wild-type MBL2 genotype patients, including the XA/XA haplotype, had increased MBL levels compared to healthy individuals. MBL deficiency was associated with decreased EFS (P = 0·03), but not with need for PICU admission. A trend for a twice increased frequency of septic shock (80% versus 38%, P = 0·14), multiple organ failure (40% versus 17%, P = 0·27) and death (40% versus 21%, P = 0·27) was observed in the absence of microbiological findings. MBL deficiency was associated with decreased EFS and possibly with an increased severity of disease during PICU admission after febrile neutropenia in the absence of any association with microbiological findings. These findings suggest prognosis to be worse in MBL-deficient compared to MBL-sufficient paediatric oncology patients.